Involving fishers in scaling up the restoration of cold-water coral gardens on the Mediterranean continental shelf. (October 2021) - Montseny, Maria; Linares, Cristina; Viladrich, Núria; Biel, Marina; Gracias, Nuno; Baena, Patricia; Quintanilla, Elena; Ambroso, Stefano; Grinyó, Jordi; Santín, Andreu; Salazar, Janire; Carreras, Marc; et al.
Abstract: Cold-water gorgonians dwelling on the continental shelf are a common by-catch of bottom-contact fishing practices. Given the slow growth and limited recruitment of cold-water gorgonians, the impact of fishing activities may seriously compromise the conservation of the highly complex coral gardens communities. For this reason, the development of effective active and passive restoration methods is nowadays a priority in order to enhance the natural recovery of impacted cold-water coral gardens. However, the ecological restoration of mesophotic and deep-sea communities remains extremely limited, due to its technological requirements and associated costs, which bring its wide-scale and long-term application into question. This study reports the preliminary results of the first large-scale active restoration of more than 400 cold-water gorgonians on the Mediterranean continental shelf. By actively involving local fishers during two consecutive fishing seasons, by-catch gorgonians were recovered and returned to the continental shelf (at 80–90 m depth). The monitoring surveys performed by using an Autonomous Underwater Vehicle (AUV) revealed that 460 gorgonian transplants survived over an area of 0.23 ha. The reintroduced cold-water gorgonian population was compared to a reference natural population in terms of size and spatial structure. The cost of the restoration amounted to 140, 000 €/ha, which is significantly lower than that of any deep-sea restoration actions performed to date. The results of this cost-effective active restoration highlight the viability of large-scale restoration of impacted cold-water coral communities, with promising results for the conservation and recovery of mesophotic and deep-sea ecosystems. Highlights: Gorgonians were recovered from by-catch and returned to the continental shelf. Photomosaic surveys showed the establishment of a reintroduced gorgonian population. By involving local fishers, the low-tech restoration method resulted in low-cost. The method allows for wide-scale application.